2019
DOI: 10.1111/ahe.12499
|View full text |Cite
|
Sign up to set email alerts
|

The expressions of some metabolic hormones (leptin, ghrelin and obestatin) in the tissues of sheep tongue

Abstract: In this study, we aimed to observe the localization and expression of peptide hormones—leptin, ghrelin and obestatin—in the sheep tongue by immunohistochemistry. For that purpose, tongues of ten adult sheep were used. Leptin expression of moderate intensity was observed in the basal and parabasal epithelial cells of the luminal epithelium, and leptin was strongly expressed in the taste buds of the circumvallate and fungiform papillae and in von Ebner's glands. Ghrelin was primarily expressed in some of the ske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 56 publications
(114 reference statements)
0
6
0
1
Order By: Relevance
“…Leptin, ghrelin ve obestatin immünoreaktiviteleri, boyamanın yoğunluğuna dayalı yarı kantitatif skorlama yöntemi kullanılarak ölçüldü (18). Bu yöntemde immunohistokimyasal skorlama (-) negatif; (+) zayıf; (++) orta veya (+++) güçlü olarak değerlendirildi.…”
Section: Yarı Kantitatif Değerlendirilmeunclassified
“…Leptin, ghrelin ve obestatin immünoreaktiviteleri, boyamanın yoğunluğuna dayalı yarı kantitatif skorlama yöntemi kullanılarak ölçüldü (18). Bu yöntemde immunohistokimyasal skorlama (-) negatif; (+) zayıf; (++) orta veya (+++) güçlü olarak değerlendirildi.…”
Section: Yarı Kantitatif Değerlendirilmeunclassified
“…Leptin is a 16 kDa single‐chain polypeptide hormone that is mainly synthesized in the white adipose tissue (Karakoç et al., 2019; Sağsöz et al., 2020). Leptin has been detected in a variety of tissue types such as placenta, mammary glands, skeletal muscle, hypothalamus and pituitary gland, using immunocytochemistry and molecular biology methods (Akbalık, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Leptin has been detected in a variety of tissue types such as placenta, mammary glands, skeletal muscle, hypothalamus and pituitary gland, using immunocytochemistry and molecular biology methods (Akbalık, 2019). Leptin plays central and peripheral roles in a wide range of metabolic activities including feed consumption and digestion, energy expenditure, thermogenesis, and the regulation of carbohydrate‐fat accumulation (Sağsöz et al., 2020). Recent studies have shown that leptin inhibits insulin secretion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations